(untitled) (Proceedings of International Educators Conference, 2023)
This article is aimed to identify the approaches employed by teachers in teaching Contemporary Children’s Literature Program to upper primary school. Using classroom observations and interview as research instruments, this paper evaluates the approaches of five ESL teachers teaching Year 5 students and examines the various challenges faced by them in the teaching of literature. Preliminary findings on the approaches revealed that the incorporation of literary elements in the classroom was minimal. Teachers were lacked creativity and fully utilized the modules provided by the Curriculum Development Centre. The Pre, While and Post-Reading was not employed effectively due to the lack of textbook provided by the school. Nevertheless, the program provides great potential for enhancing students’ language learning in the classroom. This study contributes to the field of curriculum and pedagogy for authentic learning from the evaluation of teachers’ approaches in the classroom learning.